Asia, Australia, Transnational Education and Research Networks: Implications for the ‘Anglo-Saxon Model’ - Sophie Koppe (Revue LISA)
This article will analyse how education, the Anglo-Saxon model and welfare capitalism are intertwined. It will also delve into the question of the existence of an Anglo-Saxon model of welfare capitalism. Comparing countries like the United Kingdom and Australia, which have long shared very close links, places the very existence of such a model into question. Over the last twenty years, Australia has indeed developed much more stringent welfare policies than the United-Kingdom, imposing large responsibilities on the recipients of welfare programmes and creating a very distinctive institutional set-up for the delivery of these services. Geopolitics seems to partly account for the differences between Australia and the United Kingdom. Australia is very close to Asia, and one of the strongest exchange points between those two regions is education. In this article we will see how education, and in particular transnational education in Asian countries, can be associated with the diffusion of neo-liberal ideas, especially regarding the adequate role of the state in the field of education. The first part of this article will focus on the specificities of the Australian education system, on how it has gradually integrated neo-liberal ideas. The second part of the paper will be more focused on social policy and the vision of the role of the state.